FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI PUSKESMAS SEI LANGKAI TAHUN 2024 - Shanti Hartati; Dedy Siska; Roza Erda (Ensiklopedia of Journal, 2025)
Nutritional status is a health condition that is caused by interactions between food, the body, and the environment in which humans live and is a health problem. This research aims to determine factors related to nutritional status in children under five. This research is a quantitative observational analytical study with a cross-sectional design. The total sample was 92 mothers and toddlers taken using the Non Probability sampling technique with the Total Sample method. The measuring tool uses a questionnaire. Data analysis used the Gamma Test. The research results showed that 34 toddlers (37.0%) had more nutritional status, 44 mothers of toddlers (47.8%) had good knowledge, the p-value was 0.040 0.05, 33 mothers of toddlers ( 35.9%) poor parenting style p-value of 0.038 0.05, 45 mothers of toddlers (49.0%) secondary education p-value of 0.016 0.05. The conclusion from this research is that there is a relationship between maternal knowledge, maternal parenting patterns and education with the nutritional status of children under five. Mothers of toddlers can improve the nutritional status of toddlers by meeting their basic needs. Keywords: Nutritional Status, Knowledge, Parenting Patterns, Education